JAY GATSBY’S PURSUIT OF BLISS IN THE GREAT GATSBY MOVIE SCRIPT - Tri Arie Bowo (Jurnal CULTURE (Culture, Language, and Literature Review), 2017)
The goal of life for everyone is bliss. Many ways are done to achieve bliss. However, worldly problems which appear often become an obstacle to achieve bliss itself. This thesis is the analysis results of a movie script titled The Great Gatsby which is an adaptation of the novel by F. Scott Fitzgerald. This movie script tells the story of a man named Jay Gatsby who pursues his bliss with the efforts which are done to change his social status into upper class. Jay Gatsby also wants to get his love back by trying to become a wealthy man through the achievement of the American Dream’s idea.The purpose of this thesis is to analyze The Great Gatsby movie script as a social conditions reflection of American society in the 1920s. The writer is interested in analyzing this movie script because there is the pursuit of bliss which is reflected through the main character, Jay Gatsby. This thesis focuses on the efforts of Jay Gatsby to improve his social class and achieve better situation economically and socially. In addition, the writer also analyzes marxism which exists in The Great Gatsby movie script.The method which is used in this thesis is the library research which uses movie script titled The Great Gatsby as an object of analysis. Another books which are used to look for theories and references are literary theory and criticism books, and literary research methods books. The writer also uses marxist approach to analyze the social conditions of America in the 1920s that economic growth so as to bring influence to society.The analysis results which use marxist perspective show that based on the historical background of American society, American Dream is made by society as the idea to achieve bliss with wealth, prosperity, money, glamour, and social status. They try to get wealth by doing anything whether it is legal or illegal.Key words: Jay Gatsby, pursuit of bliss,  American Dream, marxism, The Great Gatsby